The Vlachs in Macedonia in the 19th and 20th centuries - Minov, Nikola Kosto (Balcanica Posnaniensia. Acta et studia, 2021)
The article summarizes the known data about the localization and numerical distribution of various Vlach groups in Macedonia in the 19th and 20th centuries. Each Vlach group’s (Moscopolitan; Grammoustian; Farsherot and Moglenite Vlachs) migrations are analyzed separately, following them from their starting points from which they ventured forth and dispersed all over Ottoman Macedonia at the end of the 18th century, all the way to their dwellings in late 20th century in North Macedonia. In the second part of the article we review the thorough, yet unofficial statistics of Gustav Weigand and Vasil Kanchov about the number of Vlachs in Ottoman Macedonia, as well as the number and territorial distribution of the Vlachs in Macedonia, as shown in the 1921 census in the Kingdom of Serbs, Croats and Slovenes, the Yugoslav census from 1931, the six censuses conducted in socialist Yugoslavia in 1948, 1953, 1961, 1971, 1981 and 1991, and the two censuses in the Republic of Macedonia from 1994 and 2002.